INTELLIGENT CROP RECOMMENDATION SYSTEM USING MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is a major contributor to the Indian economy. The common problem existing among the Indian farmers are they don’t choose the right crop based on their soil requirements. Due to this they face a serious setback in productivity. This problem of the farmers has been addressed through precision agriculture. Precision agriculture is a modern farming technique that uses research data of soil characteristics, soil types, crop yield data collection and suggests the farmers the right crop based on their site-specific parameters. This reduces the wrong choice on a crop and increases the productivity. In this project, we are building an intelligent system, which intends to assist the Indian farmers in making an informed decision about which crop to grow depending on the sowing season, his farm’s geographical location and soil characteristics. Further the system will also provide the farmer, the yield prediction if he plants the recommended crop